The Effect of the Use of Direct Instruction, Inquiry Learning, and Project Base Learning Learning Models on the Character Value of Discipline of Students in Special Sports Class at SMA Muhammadiyah Wonosobo - Ahmad Wafi Abdulquddus1; Erwin Setyo Kriswanto2 (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to (1) identify the effect of using the Direct Instruction learning model on the discipline character values of students in the special sports class at SMA Muhammadiyah Wonosobo, (2) identify the effect of using the Inquiry Learning model on the discipline character values of students in the special sports class at SMA Muhammadiyah Wonosobo, (3) identify the effect of using the Project-Based Learning model on the discipline character values of students in the special sports class at SMA Muhammadiyah Wonosobo, and (4) determine the most effective learning model among Direct Instruction, Inquiry Learning, and Project-Based Learning in improving the discipline character values of students in the special sports class at SMA Muhammadiyah Wonosobo. This research is an experimental study using a quantitative method with a pre-experimental design, namely the one-group pretest–posttest design. In this design, a single group is given a pretest (O), followed by a treatment (X), and then a posttest. The effect of the treatment can be identified more accurately by comparing the pretest and posttest scores. The stages of the One-Group Pretest–Posttest Design include determining the sample, conducting a pretest to measure students’ initial conditions, administering the treatment, and finally conducting a posttest to identify the results of the treatment. The results of the analysis indicate that all three learning models have a positive effect on improving students’ discipline. The improvement is reflected in the overall mean score, which increased from 114.03 (pretest) to 117.99 (posttest). The improvement scores for each learning model are as follows: Direct Instruction showed a 4% increase by improving compliance through structured learning; Inquiry Learning encouraged independence and self-control through discovery processes with a 3% increase; while Project-Based Learning resulted in a 4% increase in discipline. Thus, it can be concluded that all learning models contribute to the development of discipline character values. These findings provide practical implications for physical education teachers in selecting character-based learning models that are more appropriate.